Improved Oxide Ion Conductivity of Hexagonal Perovskite-Related Oxides Ba3W1+xV1−xO8.5+x/2 - Yugo Kikuchi; Yuta Yasui; James R. Hester; Masatomo Yashima (Inorganics, 2023)
Hexagonal perovskite-related oxides such as Ba3WVO8.5 have attracted much attention due to their unique crystal structures and significant oxide ion conduction. However, the oxide ion conductivity of Ba3WVO8.5 is not very high. Herein, we report new hexagonal perovskite-related oxides Ba3W1+xV1−xO8.5+x/2 (x = −0.1, −0.05, 0.05, 0.1, 0.25, 0.4, 0.5, 0.6, and 0.75). The bulk conductivity of Ba3W1.6V0.4O8.8 was found to be 21 times higher than that of the mother material Ba3WVO8.5 at 500 °C. Maximum entropy method (MEM) neutron scattering length density (NSLD) analyses of neutron diffraction data at 800 °C experimentally visualized the oxide ion diffusion pathways through the octahedral O2 and tetrahedral O3 sites in intrinsically oxygen-deficient layers. By increasing the excess W content x in Ba3W1+xV1−xO8.5+x/2, the excess oxygen content x/2 increases, which leads to more oxygen atoms at the O2 and O3 oxygen sites, a higher minimum NSLD on the O2–O3 path, and a higher level of conductivity. Another reason for the increased conductivity of Ba3W1.6V0.4O8.8 is the lower activation energy for oxide ion conduction, which can be ascribed to the longer (W/V)–O2 and (W/V)–O3 distances due to the substitution of V atoms with large-sized W species. The present findings open new avenues in the science and technology of oxide ion conductors.